NANOSTRUCTURAL STUDIES OF SPUTTER-DEPOSITED NixAl1-x (0.5 ≤ x ≤ 1.0) ALLOY THIN FILMS - T. Joseph, Sahaya Anand; A.H.W., Ngan (Universiti Putra Malaysia, 2011)
The nanostructural characteristics of direct-current magnetron sputter-deposited NixAl1-x (0.5 ≤ x ≤ 1.0) alloy films were studied during in situ isothermal annealing in a transmission electron microscope. An expansion of the lattice by nearly 5% was observed for the Ni0.5Al0.5 and the Ni0.8Al0.2 films in their low-thickness and as-deposited state. The lattice size approaches the bulk value when the film thickness increases or after vacuum annealing heat-treatment. The Ni0.8Al0.2 films have a nanocrystalline structure in which the ordered L12 phase appears upon annealing at above 500°C. The ordered B2 phase for Ni0.5Al0.5 and Ni5Al3 phase with orthorhombic structure for Ni0.65Al0.35 were found.